Assessing the Impact of Quality of Service (QOS) Toward Urban Bus Performance in Perlis - Bakar M.F.A.; Ismail N.; Norhisham S.; Ahad N.A.; Okwonu F.Z.; Fauzi W.A.F.W.M.; Azlan N.N.I.M.; Mardi N.H.; Dullah H. (Springer Science and Business Media Deutschland GmbH, 2024)
Rapid development in industrial area were led to urbanization process and simultaneously caused heavy traffic congestion and negatively impact toward urban sustainability. High volume of traffic and prolonged congestion would continue occurred caused by high dependency toward private vehicles. Demand of daily movement from one place to another also getting increase as part of an economic development purpose. This paper will present the study of assessing the impact of quality of services (QOS) toward bus performance in Kangar, Perlis. Hentian Bas Bukit Lagi, Kangar was selected study areas as this terminal was considered as a transportation hub terminal and located at downtown Kangar. Transit Capacity and Quality of Service Manual (TCRPM) has been stated as a specific guidelines and key indicators to determine and analyzed the quality service of bus performance in selected area. Eight routes have been selected in this study. It shows that hours of service, passenger load, on time performance, and service frequency have quality of service of C, D, A and F, respectively. The overall quality of service (QOS) score for each attributes is 9. The overall quality of service (QOS) for bus performance is classified as D. The authority and operator should improve the information on bus services to the public as bus services still cater a significant number of passenger and most of the routes were tourism attraction and international boarder as well. The output of this study can be used by policy maker and bus operators on how to improve bus services in other location as well. Authorities can use these results as their feedback on measuring effectiveness of bus services in urban area. 2023, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.